Analysis of Learning Outcomes, Process Skills and Perceptions of Biology Education Students at PGRI Silampari University in the Animal Development Course Based on Project Based Learning - Mareta Widiya; Reny Dwi Riastuty; Dian Samitra (Jurnal Penelitian Pendidikan IPA, 2025)
Thehift in the learning paradigm emphasizes the importance of active student involvement through project-based learning. This research was conducted at PGRI Silampari University with 32 students as research subjects. The problem of this research is how the data on process skills, learning outcomes and perceptions of Biology Education students at PGRI Silampari University after project-based learning. The purpose of this study was to determine the data on process skills, learning outcomes, and student perceptions after learning with a project-based learning model. This research method is a descriptive method with a quantitative approach. The research instruments are observation sheets, tests, and questionnaires. The results of this study are that students achieve learning outcomes in the high category after the implementation of Project-based learning, data on students' science process skills, namely observation indicators obtained 75.25%, interpretation 67%, classification 75%, experimental planning 75%, use of tools 81.25%, predicting 77%, application of concepts 80%, communicating 100%. The average score obtained was 78.75% with a high category. Student learning outcomes in the Animal Development Course show that in general the final achievement is in the good category. Based on the final grades of 32 students, the highest score was 95.4, while the lowest was 65, with an overall average score of 78.85, which is categorized as Good. The conclusion of this study is that most students were able to achieve learning outcomes well, acquire meaningful new knowledge through problem-solving, and think critically